Body weight and low-density lipoprotein cholesterol changes after consumption of a low-fat ad libitum diet - Schaefer, E.J. (Lipid Metabolism Laboratory, Jean Mayer USDA Human Nutrition Research Center on Aging at Tufts University, Boston, MA.); Lichtenstein, A.H; Lamon-Fava, S; McNamara, J.R; Schaefer, M.M; Rasmussen, H; Ordovas, J.M (JAMA : the journal of the American Medical Association, 1995)
To assess the effects of a diet restricted in fat, saturated fat, and cholesterol, under weight-maintenance and ad libitum conditions on body weigh and plasma lipid levels in hypercholesterolemic subjects. Dietary intervention study. Twenty-seven free-living, healthy middle-aged and elderly men (n = 13, age range, 41 to 81 years) and women (n = 14, age range, 52 to 79 years) with moderate hypercholesterolemia (low-density lipoprotein cholesterol [LDL-C] greater than or equal to 3.36 mmol/L [130 mg/dL]) participated in the study. Subjects underwent three dietary phases. First, subjects were provided with a diet similar to the average US diet (baseline diet; 35.4% total fat, 13.8% to 14.1% saturated fat, and 30 to 35 mg/1000 kJ [128 to 147 mg/1000 kcal] cholesterol). During the second dietary phase, subjects consumed a low-fat diet (15.1 % total fat, 5.0% saturated fat, 17 mg/1000 kJ [73 mg/1000 kcal] cholesterol). During the baseline and low-fat diet phases, which lasted 5 to 6 weeks each, the energy intake was adjusted to keep body weight constant. During the third diet phase (low-fat ad libitum diet) subjects were given the same low-fat diet for 10 to 12 weeks, but could adjust their intake between 66% and 133% of the energy required to maintain body weight. Body weight and plasma lipid levels. Consumption of the low-fat diet under weight-maintenance conditions had significant lowering effects on plasma total cholesterol (TC), LDL-C, and high-density lipoprotein cholesterol (HDL-C) levels (mean change, -12.5%, -17.1%, and -22.8%, respectively). This diet significantly increased plasma triglyceride levels (+47.3 %) and the TC/HDL-C ratio (+14.6%). In contrast, consumption of the low-fat ad libitum diet was accompanied by significant weight loss (-3.63 kg), by a mean decrease in LDL-C (-24.3%), and by mean triglyceride levels and TC/HDL-C ratio that were not significantly different from values obtained at baseline. Our results indicate that a low-fat ad libitum diet